Examining vaccination-related adverse events in frequent neurodegenerative diseases - Shabnam Sodagari; Nassim Sodagari (Brain, Behavior, & Immunity - Health)
This study investigates adverse events following vaccination in patients with four neurodegenerative diseases: Amyotrophic Lateral Sclerosis (ALS), Alzheimer's disease, Multiple Sclerosis (MS), and Parkinson's disease. We applied advanced data processing techniques to analyze symptom patterns and severity scores across these disease groups. Patients were identified through filtering, and symptom clusters were extracted to group similar symptoms into distinct clusters, and severity scores were computed based on hospitalization and death reports. A chi-squared test was performed to assess the statistical significance of adverse event distributions among the diseases for different vaccines. The results reveal that ALS patients exhibit severe respiratory symptoms post-vaccination, while Alzheimer's patients report significant respiratory and gastrointestinal issues. MS patients commonly experience general symptoms such as fatigue, while Parkinson's patients face exacerbated motor symptoms. Notably, our analysis showed no significant difference in adverse event reporting rates between COVID-19 and pneumococcal vaccines across these disease groups. This research provides new insights into disease-specific responses to vaccines, emphasizing the importance of personalized monitoring and treatment strategies to mitigate risks and improve clinical outcomes in these vulnerable populations.